Optimalisasi Summarization Berita BBC dengan Metode BiLSTM-Transformer - Rafael Austin; Andhika Dwi Rachmawanto; Michael Jeconiah Yonathan; M Naufal Arriz; Vitri Tundjungsari (Pusat Riset dan Inovasi Nasional, 2026)
The rapid growth of digital news, such as that from the BBC, presents challenges for readers in absorbing dense information within limited time. This research proposes an automated text summarization system using a hybrid BiLSTM Transformer architecture to produce concise yet contextually accurate summaries. The model integrates BiLSTM to capture local sequential relationships and Transformer’s self-attention mechanism to handle global context, overcoming the computational limitations of standalone Transformers. Utilizing a self-embedding approach, the system processes text in an unsupervised manner, making it suitable for datasets without ground truth summaries. Evaluation was conducted using 50 samples from the Xsum dataset and 25 live BBC news links, with performance measured via cosine similarity to assess contextual preservation. The results demonstrated a consistent average cosine similarity of 0.7959 for dataset samples and 0.7877 for new data. These findings indicate that the hybrid model effectively maintains semantic integrity and provides reliable summaries for complex news articles.